Fruit production from Opuntia ficus-indica ecotypes in comparison to commercial Italian clones - Reis, C.M.G. (2018)
Fruit production, as an elementary chemical characteristic of the fruit, was evaluated in 16 Opuntia ficus-indica Portuguese ecotypes cultivated in a marginal soil without tillage, in the second and third years after plantation. The O. ficus-indica ecotypes were compared with the Italian cultivars ‘Bianca’ and ‘Gialla’. Significant differences were found among the O. ficus-indica ecotypes in biomass-related parameters and fruit yield, and different groups were established. Two spineless ecotypes (OFI-12 and OFI-13) had highest biomass production, with 9.9 Mg/ha dry matter on average. This was not significantly different from the ‘Gialla’ cultivar, which averaged 11.9 Mg/ha, for a density of 2,667 plants/ha, in the third year after plantation. Among Portuguese ecotypes, the fruit yields ranged from 2.4 to 10.1 Mg/ha fresh weight. The cultivars ‘Gialla’ and ‘Bianca’ had the highest fruit yield (13.8 and 13.6 Mg/ha fresh weight, respectively).The ‘Gialla’ cultivar and the group of ecotypes with orange pulp produced fruits of larger size and weight compared to the ‘Bianca’ cultivar and the group of ecotypes with white pulp.